Grassland in Desert Control - Singh, Ranbir (Journal of Soil and Water Conservation, 2022)
The Indian descrt occupies a large arca in the north western parts of thc country. Major land surface in Rajas- than is covered with this desert. According to Goor, the desert covers 70,000 sq. miles of the area.Rainfall in this area, on the avcragc, varies from nothing to 15 in. per year and almost 90 per cent of this rain is rcccivcd during the period mid-Junc to mid-September from the South Western monsoons. Relative humidity varies from summer to winter and morning to evening, during the different seasons, but it is quite low except during the rainy season.Hot winds of high velocities up to an average of 13 miles per hour blow during March to June period. These winds blow from west and south-west directions and carry with them sand and dust particles, causing, in other words, wind erosion. This menace of wind " dies off after the rains have set in and soon after the desert puts on a green cover of vegetation.Maximum temperature in summer shoots up to 1200F. at several points in the desert. In winters the minimum temperature sinks below freezing point. It will thus be seen how wide the range of variation of tempera- ture can be during the year. This wide range is one of the conditions that characterize the desert. Soils are generally coarse and sandy. They may be wind-blowu or locally disintegrated. The reaction of these soils is generally alkaline. The typical desert land- scape is covered with sand-dunes of different shapes and sizes. The sand-dunes may be composed of coarse sand particles, the finer particles of soils having sifted and blown away by the winds. This continuous process of sifting accounts for the generally sandy nature of the lands. There may be low-lying areas of land, where the soil may be heavier in texture and more fertile.